2006
DOI: 10.1002/jhet.5570430307
|View full text |Cite
|
Sign up to set email alerts
|

Some nucleophilic substitutions in 2‐cyano‐3‐nitroimidazo[1,2‐a]pyridine

Abstract: In some nucleophilic substitution reactions of 2‐cyano‐3‐nitroimidazo[1,2‐a]pyridine, nitrogen (alkylamines, guanidine) and oxygen nucleophiles (alkoxides) underwent substitution of the 2‐cyano group, while sulfur nucleophiles (alkylthiols) underwent substitution of the 3‐nitro group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…48 Studies of the substitution patterns in 2-cyano-3-nitroimidazole[1,2a]pyridine have shown that nitrogen and oxygen nucleophiles substitute the 2-cyano group whereas sulfur nucleophiles replace the 3-nitro group. 49 4,5-Dicyanopyridazine may react with pyrrole and indole systems as a heterocyclic azadiene in IEDDA Diels-Alder reactions. However, in acetic acid as solvent reaction occurs by substitution of CN at the 4-position and intermediates such as (10) may be isolated.…”
Section: Heterocyclic Systemsmentioning
confidence: 99%
“…48 Studies of the substitution patterns in 2-cyano-3-nitroimidazole[1,2a]pyridine have shown that nitrogen and oxygen nucleophiles substitute the 2-cyano group whereas sulfur nucleophiles replace the 3-nitro group. 49 4,5-Dicyanopyridazine may react with pyrrole and indole systems as a heterocyclic azadiene in IEDDA Diels-Alder reactions. However, in acetic acid as solvent reaction occurs by substitution of CN at the 4-position and intermediates such as (10) may be isolated.…”
Section: Heterocyclic Systemsmentioning
confidence: 99%
“…Another protocol involves the reaction of cyanamides with pyridinium salts, preliminarily obtained by microwave activation from 2‐chloropyridines and compounds containing a halomethylene group . Finally, aminoimidazo[1,2‐ a ]pyridines can be synthesized by substitution of the nitrile group with amino function in the corresponding cyanosubstituted derivatives, reduction of the nitro group in nitroimidazo[1,2‐ a ]pyridines, or direct amination of 3‐nitroimidazo[1,2‐ a ]pyridines with hydroxylamine in alcoholic alkali …”
Section: Introductionmentioning
confidence: 99%